Colloidal III–V quantum dots: a synthetic perspective. Issue 12 (9th March 2023) - Gazis, Theodore A.; Cartlidge, Ashleigh J.; Matthews, Peter D.
Abstract : III–V QDs are high performing materials, however, their exacting synthesis is a major hurdle hampering widespread adoption. We have compiled the disparate routes to III–V QDs and concisely present them, along with our perspectives for the field. Abstract : With the advent of stricter environmental regulation, quantum dots based on cadmium, lead and other heavy metals have become anathema. III–V semiconductors constitute a promising alternative because they not only match but indeed surpass the optoelectronic properties of classical quantum dot systems. Despite this fact, III–V semiconductors are no panacea. Their exacting synthesis is a major hurdle hampering widespread adoption. Several groups have risen to this synthetic challenge, resulting in a plethora of publications. In this perspective, we compile the disparate routes to III–V quantum dots and concisely present them, with pertinent examples for each synthetic methodology. This has allowed us to identify gaps in the field, which we highlight as perspectives in the conclusion.